2005
DOI: 10.1243/095440805x33225
|View full text |Cite
|
Sign up to set email alerts
|

Detection of incipient cavitation and determination of the best efficiency point for centrifugal pumps using acoustic emission

Abstract: Pumps play a significant role in industrial plants and need continuous monitoring to minimize loss of production. To date, published information on the application of acoustic emission (AE) to incipient pump cavitation has been contradictory. This article re-assesses the application of AE for detecting incipient cavitation. In addition, this paper presents results from an on-going programme to ascertain the applicability of the AE technique for determining the best efficiency point (BEP) of an operating system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 11 publications
3
35
0
2
Order By: Relevance
“…Results of this study also showed that the measurement of AE r.m.s levels could be employed for determining the BEP of pumps which offers enormous opportunities within the industry. Sikorska and Hodkiewicz [101] reiterated the observations of Alfayez [99,100] noting that AE was able to detect off duty conditions in double suction pumps. Furthermore Sikorska and Hodkiewicz noted that AE could be used to detect cavitation and recirculation and postulated that low flow AE activity was initiated by recirculation whilst high flow AE activity was due to incipient cavitation.…”
Section: Pumps and Acoustic Emission Technologymentioning
confidence: 98%
See 1 more Smart Citation
“…Results of this study also showed that the measurement of AE r.m.s levels could be employed for determining the BEP of pumps which offers enormous opportunities within the industry. Sikorska and Hodkiewicz [101] reiterated the observations of Alfayez [99,100] noting that AE was able to detect off duty conditions in double suction pumps. Furthermore Sikorska and Hodkiewicz noted that AE could be used to detect cavitation and recirculation and postulated that low flow AE activity was initiated by recirculation whilst high flow AE activity was due to incipient cavitation.…”
Section: Pumps and Acoustic Emission Technologymentioning
confidence: 98%
“…The presence of cavitation has been shown to increase operational AE noise levels. Recently Alfayez et al [99,100] undertook experimental tests on a range of pumps in an attempt to correlate incipient cavitation with AE activity. Results showed a clear relationship between AE activity measured from the pump casing, suction and discharge pipes, and incipient cavitation.…”
Section: Pumps and Acoustic Emission Technologymentioning
confidence: 99%
“…Acceleration signals have also been exploited for the detection of cavitation in centrifugal and gerotor pumps [8,9]; for this purpose, noise measurements have also often been considered [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition they observed that the audible noise of the pump decreased upon onset of cavitation. Alfayez and Mba (2004) Al Thobiani et al (2011) reported the results of experiments to predict the onset of cavitation using a range of statistical parameters derived from: the vibration signal obtained from an accelerometer on the pump casing. The airborne acoustic signal from a microphone close to the outlet of the pump and the waterborne acoustic signal from a hydrophone in the outlet pipe close to the pump were recorded.…”
Section: Introductionmentioning
confidence: 99%